Proyecto de factibilidad para la creación e instalación de una escuela particular a distancia para adultos mayores en la ciudad de Catamayo - Palacio Pauta, Edgar Daniel (2016)
In reality it is easy to see that the educational services is a huge need for many parents with no education, there are adult education center and distance but also are a great help for parents who work and can not devote themselves completely to the study, a situation that totally justifies the implementation of a center of this kind. The research proposal is developed in the Southern Region, aiming ele feasibility study for the implementation of an institution for adult education at the school level, called "Adult Education Centre Catamayo (Distance Mode)". To meet the primary objective of this study, it details the different stages that were made in the development of this work: To calculate the sample size is taken into account the implementation of a pilot survey to estimate the probabilities of relevant and irrelevant variables, which allowed to know the degree of acceptance that has the project, determining the size of the sample for this project is 250 surveys, in this case, surveys were oriented household heads, these, made up of 4 people, distributed in Catamayenses city of the province of Loja, with an estimated population of 21350 inhabitants and 5337 families. The market demand potential for this service, with the following results. For the first year of the project life is 818 unmet indicating their desire to participate effectively in the project The company offers a capacity of 73.30%, unmet demand and supply its services to cover the first 396 adult students through sixth representing 66.00% of the installed capacity. The implementation of the company will be located in a central area of the city, in the streets Isidro Ayora and May 24 (corner) a few steps from downtown Catamayenses, canton of the same name, with a total area of 210m2 ground to care for the students and will be provided with basic services essential for the normal functioning of the Adult Education Center. The financial evaluation shows the following results. According to this project NPV gives a positive value of $ 6,709.00 which indicates that the project or investment is suitable. For this project IRR is 10.45% and this value satisfactory for the project. The time required to recover the original investment would be 4 years 2 months and 12 days.